Constitutional Justice of the Right to Clean Air in Indonesia: Recognition, Protection, and State Responsibility - Elsa Diana Fartikasari; Ilham Dwi Rafiqi (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Indonesia recognizes the right to a healthy environment, yet explicit constitutional recognition of the right to clean air remains inadequate. This study analyzes the right to clean air in Indonesia through a constitutional justice perspective, emphasizing that environmental protection is not merely a regulatory matter but a manifestation of substantive justice guaranteed by the Constitution. Using normative legal analysis, the article examines the implications of Articles 28H and 33 of the 1945 Constitution and their relationship to the state’s obligation to secure air quality as part of human rights protection. The findings show that although Indonesia has enacted various environmental regulations, including the Environmental Protection and Management Law, the absence of explicit recognition of the right to clean air weakens its justiciability and limits the effectiveness of legal protection. As a result, air quality governance often remains reactive and may produce ecological inequality, particularly affecting vulnerable communities. Strengthening constitutional interpretation to affirm the right to clean air, harmonizing sectoral regulations, and reinforcing state accountability are therefore necessary to realize constitutional justice. The article concludes that recognizing the right to clean air as a constitutionally protected right is essential not only for public health and environmental sustainability, but also for ensuring equitable protection of present and future generations in accordance with Indonesia’s human rights commitments.